Quality of pediatric trauma care: development of an age-adjusted TRISS model and survival benchmarking in a major trauma center - De los Ríos-Pérez, Ana; García, Alberto Federico; Gomez, Paula; Arias, Juan José; Fandiño-Losada, Andrés (Frontiers in Pediatrics, 2024)
Background: Pediatric trauma is a major global health concern, accounting for a substantial proportion of deaths and disease burden from age 5 onwards. Effective triage and management are essential in pediatric trauma care, and prediction models such as the Trauma Injury Severity Score (TRISS) play a crucial role in estimating survival probability and guiding quality improvement. However, TRISS does not account for age-specific factors, limiting its utility for pediatric populations. This study aimed to develop a modified TRISS model (Peds-TRISS) incorporating age and to evaluate its performance relative to the original TRISS. Survival outcomes were also assessed to explore the model’s applicability across various clinical settings. These efforts align with quality improvement initiatives to reduce preventable mortality and supporting sustainable development goals. Methods: A retrospective cohort study was conducted with patients under 18 years treated at a hospital in Colombia between 2011 and 2019. Age was incorporated as a continuous variable, and logistic regression was used to calculate new coefficients for TRISS covariates. Model performance was assessed for discrimination (C statistic) and calibration, with internal validation via bootstrap resampling. Survival outcomes were analyzed using the M and Z statistics, which are commonly used for international trauma outcome comparisons. Results: Among 1,013 pediatric patients (median age 12 years, IQR 5-15; 73% male), the primary injury mechanisms were traffic accidents (31.1%), falls (28.8%), and assaults (28.7%), with an overall mortality rate of 5.7%. Peds-TRISS demonstrated good calibration (HL=9.7, p=0.3) and discrimination (C statistic=0.98, 95% CI 0.97-0.99). There was no statistically significant difference in discrimination compared to the original TRISS. The M and Z statistics (0.93 and 0, respectively) indicated no significant differences between observed and expected survival rates. Conclusions: Most fatalities occurred among adolescents and were due to intentional injuries. Peds-TRISS showed superior calibration compared to the original TRISS, aligning predicted and observed outcomes more accurately across all risk levels. These findings suggest potential for model customization to address specific populations. Prospective, multicenter studies are recommended to validate the model’s utility in diverse settings.